Detection of Trypanosoma cruzi in a Reactive Blood Bank Sample in Sonora, Mexico - Idalia Paredes-Sotelo; Mónica Reséndiz-Sandoval; Adriana Garibay-Escobar; Edgar Alfonso Paredes-González; Aracely Angulo-Molina; Angel Ramos-Ligonio; Eric Dumonteil; Claudia Herrera; Olivia Valenzuela (Tropical Medicine and Infectious Disease)
Chagas disease is a neglected disease caused by the parasite Trypanosoma cruzi, a public health problem in both endemic and non-endemic countries. In Mexico, the southern region is considered endemic, and cases are frequently reported; however, in the northwestern region, only a few cases are confirmed annually. This study describes, for the first time, the Discrete Typing Unit (DTU) of Trypanosoma cruzi in a volunteer blood donor rejected for being reactive in the northwestern region of Mexico. Seroreactivity was confirmed using “in-house” ELISAs which employed three different antigens: total extract from Trypanosoma cruzi isolated from a vector (Triatoma rubida) from Sonora (strain T1), strain H1 and CL-Brener. The molecular characterization of Trypanosoma cruzi was conducted by amplifying satellite DNA by qPCR and posterior sequencing of the mini-exon gene, using Next Generation Sequencing (NGS) to enhance the accuracy of genetic characterization. The results show that the reactive status of this blood donor was confirmed using our in-house ELISAs, and the presence of Trypanosoma cruzi by detecting TcI DTU confirmed the infection status.